Genomology versus Biology (British Journal of Multidisciplinary and Advanced Studies, 2023)
Genomology is one of the branches of natural science emerged with the establishment of Genome Model by dismissing fake sciences of Biology together with its erroneous and inseparably paired terms called living-thing & nonliving-thing. The key objective of this study is to forward/display nondisputable and concrete evidences or reasons for the fact that Biology is irreversibly dismissed, being replaced by Genomology and to conclude that hereafter, global academic system of genomic-things must be functional at all levels of teaching & learning with sciences of Genomology. The targetful strategy of the study is designed/summarized or entitled Methodology & Results. Indeed, Genomology is a Giant Ethiopian Science of educational asset contributed to all human races of the world by dismissing fake sciences of Biology that has been paralyzing scientific progresses of student children of all human races of the entire world for several centuries. Genome is the unit of both structure & function of all genomic-things. Genome is also the unit of evolutionary change of all genomic-things.